The gadamerian interpretation of Dilthey regarding the transcendental status of hermeneutics - Catoggio, Leandro (2012)
This paper aims to show two things. On the one hand, it aims to discover that the interpretation executed by Gadamer of the Dilthian hermeneutic project ends up being one sided and reductionist in several respects, and therefore does not do justice to the fundamental hermeneutical plan of the critique of historical reason. Furthermore, we will show how Gadamerian hermeneutics continue with the Dilthian project assimilating trascendental elements that, ultimately, structurally operate the philosophical hermeneutics.